Incidencia de la comunicación y satisfacción de las necesidades humanas en el logro de las competencias reales - Paredes Riera, Julio Vicente (2015)
Recognizing elements overly influential inherent to the process of formation that have been neglected in the study for other areas allows appraisal of the actual performance and the factual evidence of achievements through achieving real powers, massive communication and satisfaction of basic human needs as generators architects of the dynamic teaching and learning within and outside the classroom contributing to sustainable with professionals, academic products that the wording of good living will provide planning and action for the individual, society and the institution.